EVALUATION OF SERUM ELECTROLYTE AND LIPID PROFILE ALTERATIONS IN MALE WISTAR RATS ADMINISTERED ALMOND (Terminalia catappa) AND CASHEW NUT (Anacardium occidentale) OILS - Njideaka, Ogochukwu Tracy (FUDMA Journal of Sciences, 2026)
Natural plant oils rich in unsaturated fatty acids and bioactive compounds are increasingly explored as safer alternatives to conventional dietary lipids due to their cardiometabolic benefits. This study evaluated the effects of almond (Terminalia catappa) and cashew nut (Anacardium occidentale) oils on serum electrolyte balance and lipid profiles in healthy male Wistar rats. Twenty rats (135–160 g) were randomly assigned into five groups (n = 4): control, T. catappa (200 and 400 mg/kg), and A. occidentale (200 and 400 mg/kg). Oils were administered orally for 28 days, after which serum samples were analyzed for lipid parameters and electrolytes using spectrophotometric methods.Results showed no significant changes (p > 0.05) in total cholesterol, HDL-C, triglycerides, and VLDL-C across treated groups compared with control. Notably, T. catappa at both doses and A. occidentale at 400 mg/kg significantly reduced serum LDL-C (p < 0.05), suggesting potential cardioprotective properties. Serum sodium, chloride, phosphorus, and bicarbonate levels remained within normal physiological ranges, indicating preserved electrolyte and acid–base homeostasis. However, significant potassium elevation was observed with A. occidentale at 400 mg/kg (p < 0.05).In conclusion, short-term administration of T. catappa and A. occidentale oils is largely metabolically safe in healthy rats, with minimal impact on serum lipids and electrolytes. The LDL-C reduction, particularly with T. catappa, highlights cardioprotective potential, while potassium elevation with high-dose cashew oil warrants further investigation. These findings support both oils as safe dietary or therapeutic lipid sources.